2022
DOI: 10.1101/2022.11.08.515541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular diversity and connectivity of accessory olfactory system neurons

Abstract: Olfaction is the primary sensory modality by which most vertebrate species interpret environmental cues for appropriate behavioral outputs. The olfactory system is subdivided into main (MOS) and accessory (AOS) components which process volatile and non-volatile cues. While much is known regarding the molecular diversity of neurons that comprise the MOS, less is known about the AOS. Here, focusing on the AOS which is largely comprised of the peripheral vomeronasal organ (VNO), the accessory olfactory bulb (AOB)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Nevertheless, the previous description we made of early (E8.5) Dbx1-expressing progenitors contributing to a subset of cranial neural crests cells (Causeret et al, 2011) could support a certain degree of overlap between the two lineages. Furthermore, a recent preprint investigating the cellular diversity and connectivity patterns in the accessory olfactory system reported that Dbx1-driven diversity is not only observed in the VNO but also in the accessory olfactory bulb and medial amygdala (Prakash et al, 2022). This work points to the idea of a molecular code involved in the assembly of olfactory circuits that would be conserved from the sensory epithelia to the central processing structures.…”
Section: Diversity Among Sensory Olfactory Derivativesmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, the previous description we made of early (E8.5) Dbx1-expressing progenitors contributing to a subset of cranial neural crests cells (Causeret et al, 2011) could support a certain degree of overlap between the two lineages. Furthermore, a recent preprint investigating the cellular diversity and connectivity patterns in the accessory olfactory system reported that Dbx1-driven diversity is not only observed in the VNO but also in the accessory olfactory bulb and medial amygdala (Prakash et al, 2022). This work points to the idea of a molecular code involved in the assembly of olfactory circuits that would be conserved from the sensory epithelia to the central processing structures.…”
Section: Diversity Among Sensory Olfactory Derivativesmentioning
confidence: 78%
“…Furthermore, a recent preprint investigating the cellular diversity and connectivity patterns in the accessory olfactory system reported that Dbx1-driven diversity is not only observed in the VNO but also in the accessory olfactory bulb and medial amygdala (Prakash et al, 2022). This work points to the idea of a molecular code involved in the assembly of olfactory circuits that would be conserved from the sensory epithelia to the central processing structures.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, it is worth mentioning that we previously described a partial overlap between Wnt1 and Dbx1 lineages (Causeret et al., 2011) as well as a regulatory loop between Pax7 and Dbx1 (Gard et al., 2017). Furthermore, a recent preprint investigating the cellular diversity and connectivity patterns in the accessory olfactory system reported that Dbx1‐driven diversity is not only observed in the VNO but also in the accessory olfactory bulb and medial amygdala (Prakash et al., 2022). This work points to the idea of a molecular code involved in the assembly of olfactory circuits that would be conserved from the sensory epithelia to the central processing structures.…”
Section: Discussionmentioning
confidence: 99%